DESENVOLVIMENTO E CARACTERIZAÇÃO DE UMA NOVA BLENDA POLIMÉRICA DE POLI(METIL METACRILATO)-POLI(ETILENOGLICOL) PARA PRODUÇÃO DE NANOCÁPSULAS E APLICAÇÃO EM DRUG DELIVERY - Santos, Cayane Genro (2017)
Polymers are part of our life and have many applications in different branches of industry. In pharmaceutics they are widely used in systems for the modified release of drugs. Polymer blends appear as an alternative to the use of individual polymers and have been utilized to produce nanocarriers. In the present study a polymeric material was developed to respond to a specific aim of the pharmaceutical industry, which is the sustained release of drugs. For this purpose, for the first time, a polymeric blend of poly(methyl methacrylate) - polyl(ethylenoglycol) (PMMA-PEG) was developed for the production of nanocapsules and the appication for the sustained delivery of a model-pharmaceutical, in this case, simvastatin. Tests were also performed for the characterization and stability of this nanostructure. Further, the cyto and genotoxicity of the nanocapsules in mononuclear cells of peripheral blood was evaluated, and an intermediate product was developed (nanocapsules of powdered simvastatin) to be used later by the pharmaceutical industry. The polymer blend of PMM-PEG was obtained with a high yield, 94 ± 3.7%. The infrared spectrum shows the typical bands at 3349 cm-1 and 2922 cm-1 corresponding to the vibration of the lengthening of -O-H and -C-H bonds. Characteristic bands at 1731 and 1102 cm-1 were attributed to -C=O and -C-O-C lengthening. In the 1H-RMN spectrum the sign of methylenic protons was observed at 3.68 ppm (-CH2OCH2-) of PEG and the peak at 3.61 ppm of the protons of cluster -OCH3 of PMMA. The molecular weight determined by GPC was 101.581 Da and the polydispersion index was 5.342. Analyses of DSC suggested that the mixture is a molecularly well dispersed system, and the curves of TGA indicated two weight losses in relation to both polymers. The nanocapsules produced by the polymeric blend presented a particle size and polydispersion index of 198.2 ± 1.4 nm and 0.08 ± 0.01 for the white nanocapsules and 194.4 ± 1.7 nm and 0.07 ± 0.00 for the nanocapsules with simvastatin. The zeta potential value was -11.22 ± 3,01 mV for the nanocapsule with simvastatin and -9.19 ± 0.26 mV for the white nanocapsules, and efficiency of simvastatin encapsulation was high, 98.64 ± 0.00%. The condition of refrigerated storage (± 4 ºC) was what best ensured the preservation of the physicochemical characteristics of the suspensions over 90 days. The cyto and genotoxicity tests indicated that the samples tested were not toxic and, therefore, are safe for biomedical application. The release of the drug from the nanocapsules was more sustained than its free form and the presence of PEG in the polymer blend of PMMA-PEG modified the release mechanism and increased the quantity of simvastatin released compared to the nanocapsules produced only with PMMA. Forty-five per cent release of simvastatin was observed in 24 hours, from the nanocapsules produced by the PMMA-PEG blend, and 34% from the capsules produced only with PMMA., while the non-encapsulated simvastatin was fully released in 17 hours. Finally, the suspensoins were efficiently dried by spray-drying, and resulted in an intermediate product with a yield of 66.83% and presented adequate physicochemical characteristics. Thus, we can conclude that the polymer blend was obtained successfully through a simple, efficient process, and served to develop a nanocarrier of drug.s The nanocapsules produced by the polymer blend promoted a sustained release of the drug, indicating that these nanocapsules are good candidates for use as drug carriers.